Some tips for preparation of E. coli competent cells - Zhao, Lin; Wang, Huan; Jia, Yukun; Yang, Xianyu (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
In this study, we modified the protocol of E. coli competent cell (CC) preparation on two aspects. One is shortening centrifuge time to 2 min instead of 15 min (used in the traditional method), by which the exposure time of cell in solutions for CC preparation was shortened, and the chemical or biological damage on cells could be minimized. The other is suspending cells with disposable Pasteurized pipette instead of micropipette tips to diminish physical damage on cells. By this modified protocol, CC average transformation efficiency of two batches is 1.88×108 and 2.07×108, respectively, 10 times higher than that of CC prepared by traditional method.